Hierarchy robust control for unmanned quadrotor helicopter without linear velocity measurement. (2016) - Zhao, Long; He, Zefang; Zeng, Yulong
Considering the parameter measurement errors of a low-cost quadrotor system and the constant wind disturbance during flight, a hierarchy robust control strategy for unmanned quadrotor helicopter is constructed. The hierarchy robust control strategy is that the attitude and position loops of the quadrotor adopt different robust control strategy. The integral backstepping controller is applied to stabilise the attitude angles of the quadrotor with parameter errors. The linear robust controller with a compensator for the constant wind is applied to fulfil the position tracking. Sliding mode observer for the quadrotor position subsystem is founded to estimate the linear velocity when the direct measurement is unavailable. The simulating test is implemented and the simulation test results show that the control algorithm is stable and can effectively reject the constant wind disturbance and have strong robustness to the parameter errors.